Contributions of John Dewey and Immanuel Kant's Thought in Formulating Islamic Education Objectives - Ahmad Isa Abdallah Ahsa; Abdul Khobir (Social Journal of Studies in Education, 2025)
The formulation of Islamic education objectives represents one of the most critical challenges in contemporary Islamic pedagogy. This research explores the significant contributions of John Dewey's pragmatism and Immanuel Kant's philosophical thought in constructing a comprehensive framework for Islamic education objectives. Through a critical literature review approach, this study examines how Dewey's emphasis on experiential learning and social relevance, combined with Kant's categorical imperative and moral philosophy, can enrich the traditional understanding of Islamic education objectives. The findings demonstrate that Dewey's concept of learning by doing and problem-solving methodology complement Islam's emphasis on wisdom (al-hikma) and the practical application of knowledge, while Kant's duty-based ethics align with the Islamic concept of moral responsibility (amanah). This research concludes that integrating these Western philosophical perspectives with Islamic education principles creates a holistic framework that emphasizes not only the transmission of knowledge but also the development of ethical consciousness, critical thinking, and social responsibility. The synthesis of these three philosophical traditions offers new possibilities for contemporary Islamic education in addressing modern educational challenges while preserving Islamic values and principles. This research contributes to the formulation of an innovative and inclusive Islamic educational model in which philosophical dialogue between Western and Islamic intellectual traditions establishes robust academic grounds for curriculum reform and pedagogical innovations that effectively address the demands of both local and global educational contexts.